2017
DOI: 10.5539/ijsp.v7n1p99
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Heterogeneity of Time -to- Recovery from Obstetric Fistula Patients; Comparison of Acceleration Failure Time and Parametric Shared Frailty Models.

Abstract: Obstetric Fistula is a medical condition that involves an opening or perforation between the vagina and the bladder or the vagina and the rectum. It is a serious, life threatening and often debilitating medical condition that affects thousands of women in developing countries.The study consists of 270 obstetric fistula patients having all required information who were taking treatment at Jimma University Specialized Hospital in south west Ethiopia from January, 2011 to January ,2017. The log-rank and generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…A similar conclusion was drawn from research carried out in Gondar [15], Addis Ababa, and developing countries [14,22,23]. Moreover, similar to the results of the present study, a study from Jimma University revealed that RVF patients recover more quickly than VVF patients [24].…”
Section: Discussionsupporting
confidence: 92%
“…A similar conclusion was drawn from research carried out in Gondar [15], Addis Ababa, and developing countries [14,22,23]. Moreover, similar to the results of the present study, a study from Jimma University revealed that RVF patients recover more quickly than VVF patients [24].…”
Section: Discussionsupporting
confidence: 92%
“…Data were collected by four data collectors using an English‐version structured data abstraction checklist, after review of different kinds of literature and previous similar studies, 8–12 which was organized according to the objective of the study. The collected data were coded, entered, cleaned, and checked for clarity, consistency, and completeness up to the end of each data collection period.…”
Section: Methodsmentioning
confidence: 99%
“…If the patient was recovered from a surgical repair of obstetric fistula within 21 days following surgery it was considered as an event of interest, and if the patient was not recovered from a surgical repair of obstetric fistula within 21 days following surgery or if the patient had died following an operation it was considered as censored. 15 Data were collected by four data collectors using an Englishversion structured data abstraction checklist, after review of different kinds of literature and previous similar studies, [8][9][10][11][12]…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
See 2 more Smart Citations